A Comparison of Clinical Outcomes of Single Versus Two Miniplate Fixation of Parasymphysis Fracture - Safoora Hashmi, Asif Nazir Ch., Inqalab Fareed, Sahrish Liaqat, Muhammad Abi Waqas, Fareed Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Many methods have been discovered to treat the fracture of parasymphysis region of mandible i.e., using miniplates. However not many studies have been done to prove the good clinical outcomes of one miniplate versus two miniplates. Aim: The purpose of the study is to compare the clinical results of one miniplate vs two miniplate for the parasymphysis of mandible. Material and Methods: 20 patients were treated with single miniplate and 20 for 2 miniplates. Many outcomes variable after surgery such as post-surgical scar, mental nerve paresthesia, need for plate removal and interincisal opening were calculated and interpreted using chi square test. Results: All outcome variables such as post-surgical scar, mental nerve paresthesia, need for plate removal and interincisal opening did not show any statistically significant relation with both groups(P value >0.05). Conclusion: Both types of miniplate ensure osseous healing but depending upon the individual factors such as mandible height and bio mechanics pattern should be considered before deciding scheme of treatment for an individual. Keywords: miniplate fixation, parasymphysis mandible, osteosynthesis.